Modelling and simulation of edoxaban exposure and response relationships in patients with atrial fibrillation - Salazar, Daniel E.; Mendell, Jeanne; Kastrissios, Helen; Green, Michelle; Carrothers, Timothy J.; Song, SaeHeum; Patel, Indravadan; Bocanegra, Tomas S.; Antman, Elliott M.; Giugliano, Robert P.; Kunitada, Satoshi; Dornseif, Bruce; Shi, Minggao; Tachibana, Masaya; Zhou, Simon; Rohatagi, Shashank (Thrombosis and Haemostasis, 2012)
Edoxaban is a novel, orally available, highly specific direct inhibitor of factor Xa and is currently being developed for the treatment and prevention of venous thromboembolism and prevention of stroke and systemic embolism in patients with non-valvular atrial fibrillation (NVAF). The objectives of the present analyses were to characterise edoxaban population pharmacokinetics (PPK) and identify potential intrinsic and extrinsic factors affecting variability in edoxaban exposure, determine if there are relationships between edoxaban pharmacokinetics or biomarkers and the risk of bleeding in patients with NVAF using an exposure-response model, and to use the PPK and exposure-response model to support dose selection for a phase III trial of edoxaban in patients with NVAF. PPK analysis of data from 1,281 edoxaban-dosed subjects with intrinsic factors such as renal impairment or NVAF and extrinsic factors such as concomitant medications revealed significant effects of renal impairment and concomitant strong P-glycoprotein (P-gp) inhibitors on the pharmacokinetics of edoxaban. Exposure-response analysis found that in patients with NVAF, the incidence of bleeding events increased significantly with increasing edoxaban exposure, with steady-state minimum concentration (Cmin,ss) showing the strongest association. Clinical trial simulations of bleeding incidence were used to select 30 mg and 60 mg once-daily edoxaban with 50% dose reductions for patients with moderate renal impairment or receiving concomitant strong P-gp inhibitors as the treatment regimens in the ENGAGE AF-TIMI 48 (NCT00781391) trial.The results of this study were previously presented at the 2009 International Society on Thrombosis and Haemostasis, July 2009, Boston, Massachusetts, USA.
Keywords: Edoxaban; factor Xa inhibitor; atrial fibrillation; population pharmacokinetics